The Relationship between High Heel Size Variation and Long Standing Duration on the Risk of Plantar Fasciitis - Gusnur Gazali Ashari; Benny Benny; Iman Dwi Winanto (Indonesian Journal of Global Health Research, 2026)
Wound healing is a crucial aspect in orthopedics. Channa striata (snakehead fish) contains albumin and other bioactive compounds thought to accelerate wound healing To assess the effectiveness of Channa striata extract gel on wound healing in Wistar rats based on clinical (wound area) and histopathological (HEALS-A score) parameters. Laboratory experimental research with post-test only control group design using 27 male Wistar rats, divided into three groups: negative control (no treatment), positive control (Bioplacenton), and treatment (Vipalbumin gel). Evaluation of wound area was performed on days 0, 3, 7, and 14 using ImageJ. Histopathological examination was conducted using HE staining and HEALS-A scoring. Data were analyzed using ANOVA and Chi-Square tests.  On day 14, the mean wound area of the treatment group (7.1±2.8 mm²) was equivalent to the positive control (6.7±2.5 mm²), both significantly smaller than the negative control (54.2±32.5 mm²; p<0.001). HEALS-A scores showed significant differences between groups on days 3, 7, and 14 (p<0.001; p=0.001; p=0.001). Channa striata extract gel effectively accelerates wound healing clinically and histologically, with effectiveness equivalent to Bioplacenton.